(untitled) - Zarnay, Pavel; Bednar, Juraj; Chalupka, Stefan; Moravcik, Jozef (Doprava a spoje, 2010)
River informations services (RIS) are harmonised communication and information systems for inland shipping and cargo ship transport in continuity to other transport and forwarding modalities. On Danube and in Slovakia, they are also realised through ship, coast, central and management segments. They provide information about inland waterway and its traffic, port and waterway usage fees, support for navigation management and accident assistance as well as support for statistics, customs services and business inland shipping activities.